(untitled) (Theatrum historiae, 2008)
The author deals with official houses Nr. 3 in Jiráskova street and Nr. 61 on the Smetana’s square in Litomyšl (East Bohemia). Both the buildings are interpreted – using the analysis of decoration of the facades – to be the works of constructor Jiří Béba. He functioned in Litomyšl in the last third of 18 century. According to archival sources he built several building for local establishment (the Litomyšl estate was in possession of the counts Waldstein-Wartenberg) – these were a church in Čistá, a parsonage in České Heřmanice, some forester’s lodges, etc. Thanks to the formal analysis we can extend the circle of his works – he constructed also the two above mentioned official houses, so called „Pernstein“ granary on the periphery of the town and two houses on the Brauner’s square.